Promoting students’ conceptual change by ıntegrating the 3-2-1 reading technique with refutation text in the physics learning of buoyancy - Djudin, Tomo (Journal of Turkish Science Education, 2021)
The conceptual change is assumed a potential teaching pedagogy to prepare the skills for anticipating 21th century. This quasy-experimental method with pre-and posttest control group design was applied to examine the effectiveness of integrating 3-2-1 reading technique with refutation text on students’ conceptual change of buoyancy.The subjects consist of 39 eleventh grade students of senior high school which was drawn by using intact group random sampling technique.The diagnostic test consists of nine items of multiple choice with two distractors which followed by supporting reasons was administered. The study found various profiles of students’ misconseptions of buoyancy. The reduction of students’ misconceptions after the treatment was 54,71 %. A significant conceptual change of buoyancy was occured among students after the treatment. The extent of effectiveness of the treatment was high category (gain mean = 0,82). A science teaching should intentionally model a conceptual change strategy in schools.